Training and Reward for Teacher Performance Moderated by the Work Environment at Bina Bangsa Mandiri School - Raden Adhi Susatyo Notodisuryo; Askardiya R. Adji (Journal AGENCY, 2025)
Training, rewards, and work environment are factors that are thought to influence teacher performance. This study aims to analyze the effect of training and rewards on teacher performance at Bina Bangsa Mandiri School, with the work environment as a moderating variable. The study was conducted on 60 educators with a saturated sampling technique. Data collection used questionnaires distributed offline, then processed using the Partial Least Square - Structural Equation Modeling (PLS-SEM) method. The results of the study showed that training and rewards had a significant effect on teacher performance. This means that the better the training and rewards given, the higher the teacher's productivity and competence. However, the work environment does not moderate the relationship between training and performance, but moderates the relationship between rewards and teacher performance. Thus, rewards will be more effective if given in a conducive work environment, both physically and non-physically.